Análisis del desempeño de empatía a un grupo de niños a través de un videojuego (2019)
The objective of this research is to identify if there is a relationship between the empathy evaluated in two tests called empathy for pain and conflict resolution vs the Video Game 2.0. To this end, a descriptive study was established for a group of 14 randomly selected children belonging to an educational institution in the city of Cali. The research was approached from the concepts of empathy, social cognition, videogaming and conflict resolution. The conceptual reference that supports this research was taken from the theory of Caillois (1997), in relation to the concept of reality vs. fiction and different investigations for the concept of empathy. Methodologically an analytical empirical study was carried out, with descriptive scope, making use of the tool that evaluates executive functions and social interaction, called visor 2.0. SPSS, statistical software that offers data collection techniques, was used to analyze the data. The findings allow us to conclude that if there is a similarity between the subject's real life and virtual reality, there was also a significant relationship between empathy and the negative interactions evaluated in the video game visor 2.0.